Simulation of gait asymmetry and energy transfer efficiency between unilateral and bilateral amputees - Aslani, N.; Noroozi, S.; Khoo, S.Y.; Ong, Z.C.; Maggs, C. (Springer Verlag (Germany), 2016)
Efficient walking or running requires symmetrical gait. Gait symmetry is one of the key factors in efficient human dynamics, kinematics and kinetics. The desire of individuals with a lower-limb amputation to participate in sports has resulted in the development of energy-storing-and-returning (ESR) feet. This paper analyses a case study to show the effect of symmetry and asymmetry as well as energy transfer efficiency during periodic jumping between simulated bilateral and unilateral runners. A custom gait analysis system is developed as part of this project to track the motion of the body of a physically active subject during a set of predefined motions. Stance and aerial times are accurately measured using a high speed camera. Gait frequency, the level of symmetry and the non-uniform displacement between left and right foot and their effects on the position of the Centre of Mass (CM) were used as criteria to calculate both peak energies and transformation efficiency. Gait asymmetry and discrepancy of energy transfer efficiency between the intact foot and the ESR are observed. It is concluded that unilateral runners require excessive effort to compensate for lack of symmetry as well as asymmetry in energy transfer, causing fatigue which could be a reason why bilateral amputee runners using ESR feet have a superior advantage over unilateral amputees.